Targeted Poverty Alleviation and Children's Academic Performance in China - Huifu Nong; Qing Zhang; Hongjia Zhu; Rong Zhu (Institute of Labor Economics (IZA), 2021)
This paper estimates the causal impact of China's targeted poverty alleviation program on the academic achievement of students from poor households. We use the longitudinal academic records of a cohort of students from all middle schools in a nationally designated poor county in China. Using the difference-in-differences approach, we show that targeted poverty alleviation improves the scholastic performance of girls and their achievement rank among peer students. However, we find no such empirical evidence for boys. Our findings suggest that the new anti-poverty program in China has the potential to ameliorate the intergenerational transmission of low socioeconomic status to girls by promoting their human capital accumulation.
Keywords: I21; I32; I38; 330; targeted poverty alleviation; academic outcomes; middle school; China